Local production, characterization, and performance of pozzolanic fly ash-based granulated coal ash (GCA) - Bugay, Sefina Glisa M.; Francisco, Dianne B.; Orozco, Christian R.; Resurreccion, Augustus C. (Quezon City College of Engineering, University of the Philippines Diliman, 2018)
Granulated Coal Ash (GCA) was produced with locally available waste material pozzolanic fly ash, combined and granulated with blended Type 1P cement and water. It was physically and chemically characterized along with the raw fly ash used for its production. Chemical and physical components of the local GCA were identified. The effectiveness of the local GCA in remediation of the Estero de San Miguel was also tested through batch experiments with the wastewater and sediment samples from the area. Physical and chemical parameters (pH, ORP, Turbidity, etc.) and the amount excessive nutrients present in the samples were measured after every 7th day to understand how the local GCA can affect the wastewater samples and the sediments through time. It was noted that the GCA has the capability to neutralize the wastewater, thus maintaining the normal status of the water, and reducing the consumption of oxygen in the process. This can lead to a better environment for the microorganisms to live in. The local GCA also serves as a wall between the sediments below and the wastewater above it. It blocks the exchange of excess nutrients from the sediments to the water above it by adsorbing them through the porous surface of the GCA. Thus, before even being released to the wastewater, excess nutrients undergo chemical mixing with the Calcium from the GCA producing less harmful salts and acids.
Thesis (Bachelor of Science in Civil Engineering)--University of the Philippines Diliman
Keywords: Coal ash; Fly ash